Control Circuitry for a Partial Series Resonant Converter - Feno, Ivan; Jadron, Eduard; Spanik, Pavol (Communications - Scientific Letters of the University of Zilina, 2001)
A control circuit for a new high-frequency DC-DC converter, suitable for application in a few kilowatts range, is presented. The converter topology is based on a half bridge series resonant converter, i. e. having only two switches. Resonance occurs only for a part of each switching cycle, and a discrete energy pulse is transferred to the load every half cycle, rendering a variable frequency controller for controlling the output power. The converter features zero-voltage turn-on and snubbed turn-off at reduced current for the switching devices, and zero current commutation of the rectifier diodes, making it suitable for IGBT switches operating at a switching frequency higher than 20 kHz. The efficiency of the converter is supposed very high under full load and low load conditions, while the dynamic output voltage range is two times larger than that of the conventional half bridge Series Resonant Converter. PSpice Model presents the entire converter and control circuit.
Keywords: no keywords